Cellular and Molecular Mediators of Neuroinflammation in the Pathogenesis of Parkinson’s Disease - Sandeep Vasant More; Hemant Kumar; In Su Kim; Soo-Yeol Song; Dong-Kug Choi (Mediators of Inflammation)
Neuroinflammation is a host-defense mechanism associated with restoration of normal structure and function of the brain and neutralization of an insult. Increasing neuropathological and biochemical evidence from the brains of individuals with Parkinson’s disease (PD) provides strong evidence for activation of neuroinflammatory pathways. Microglia, the resident innate immune cells, may play a major role in the inflammatory process of the diseased brain of patients with PD. Although microglia forms the first line of defense for the neural parenchyma, uncontrolled activation of microglia may directly affect neurons by releasing various molecular mediators such as inflammatory cytokines (tumor necrosis factor-α, interleukin [IL]-6, and IL-1β), nitric oxide, prostaglandin E2, and reactive oxygen and nitrogen species. Moreover, recent studies have reported that activated microglia phagocytose not only damaged cell debris but also intact neighboring cells. This phenomenon further supports their active participation in self-enduring neuronal damage cycles. As the relationship between PD and neuroinflammation is being studied, there is a realization that both cellular and molecular mediators are most likely assisting pathological processes leading to disease progression. Here, we discuss mediators of neuroinflammation, which are known activators released from damaged parenchyma of the brain and result in neuronal degeneration in patients with PD.